An Analysis and Translation of Selected Filipino Elegy - SIPLAC, GRACE (International Journal of Arts, Sciences and Education, 2022)
The focus of this investigation was on the analysis and translation of a particular elegy concerning the passing of a loved ones, friends and oneself. The purpose of this study is to translate an English elegy into Filipino, analyze and gain an understanding of the lessons that can be gained from each of the selected elegies, and become familiar with the specific values that can be gained from each elegy when those lessons are applied to the lives of the people. According to the findings, it is possible to draw the conclusion that the English language conveys a significant amount when it is translated into Filipino. The participants' relationships with one another and with God are two of the aspects of their life that are brought up in the elegy readings that are presented here. Aside from that, the researcher makes the discovery that the chosen elegy has a number of important life lessons to be gained from it. Therefore, it is strongly recommended that institutions, whether public or private educational establishments, need to look at and include the elegy as one of the topics to the subject like literature and social studies. This recommendation applies to both public and private educational establishments. Perform a thorough investigation of elegy. Continue to spread the word about elegy by hosting poetry contests with a variety of topics. These contests should be open to the public and should be read aloud to others in order to alleviate pain not only for the individual but also for the person's loved one.